STATE OF THE SYMPATHETIC-ADRENAL SYSTEM IN MENOPAUSAL WOMEN WITH METABOLIC SYNDROME - Tashtemirova I. M. (Scholar Express Journals, 2024)
The aim of this work was to study the relationship of disorders of the functional state of the sympathetic-adrenal system in women in the menopausal period with metabolic syndrome. The results of the conducted studies showed that in the metabolic syndrome, the sympathetic-adrenal system and lipid peroxidation processes are activated. With the onset of menopause, women with hypertension have an increase in the average daily systolic blood pressure, as well as the rate and magnitude of its morning rise, which are more pronounced in the postmenopausal period. The formation and development of hypertension in women in the menopausal period occurs against the background of activation of the sympathetic nervous system.
Keywords: Metabolic syndrome; menopausal syndrome; sympatho-adrenal system; arterial hypertension.